Academic freedom: How to conceptualize and justify it?. (May 2022) - Kabasakal Badamchi, Devrim
This article deals with the question of how academic freedom can be conceptualized and justified. First, I analyze two conceptions of academic freedom: institutional autonomy and intellectual and professional autonomy. I claim that institutional autonomy is a limited way to conceptualize academic freedom because there is no guarantee that institutions always favor freedom of intellectuals. In line with this, I argue that academic freedom as intellectual and professional autonomy should be the prior, if not the only, conception of academic freedom. Second, I examine critically different justifications of academic freedom that provide us with reasons to attach high protection to academic freedom as a particular right. I contend that the justification of the university as a realm of discovery of truth and independent knowledge production has to be complemented with the justifications of the university as a realm of democratic free debate and the autonomy of academics to speak freely. This is because, the discovery of truth argument alone does not require us to accept any moral principle other than skepticism about our own beliefs, which is not a strong ground for free speech on its own. Third, I argue that equal autonomy provides a good reason for academic freedom by emphasizing the rights of academics to speak in line with what they believe is true and only in this way can they contribute to the democratic debate in academia. This line of reasoning endorses the value of the search for truth and knowledge too since it is only possible for academics to perform the profession of search for truth when they are able to speak, write and research freely.